A cseh szak 50 éve (1955–2005) (50 years of the Czech Department 1955–2005): Ed. Heé Veronika, Oleg Fedoszov. Budapest: ELTE BTK, Szláv Filológiai Tanszék, 2007. 207 pp. - Janiec-Nyitrai, Agnieszka (Slavia Centralis, 2020)
The book A cseh szak 50 éve (1955–2005) (50 Years of the Czech Department 1955–2005) contains the proceedings from a conference held on the 14th and 15th of November, 2005.